DIRECTIONS TO IMPROVE GENERALIZED INDICATORS OF THE ECONOMIC EFFICIENCY OF AN INDUSTRIAL ENTERPRISE (British Journal of Global Ecology and Sustainable Development, 2023)
The application of new innovations and technologies in Network Enterprises is carried out through indicators such as gross income, profit and net income, as well as the assessment of the economic efficiency of the Enterprise.